A theory of adaptation - Hutcheon, Linda (Routledge, 2013)
A Theory of Adaptation explores the continuous development of creative adaptation, and argues that the practice of adapting is central to the story-telling imagination. Linda Hutcheon develops a theory of adaptation through a range of media, from film and opera, to video games, pop music and theme parks, analysing the breadth, scope and creative possibilities within each.